Homogeneous and heterogeneous catalytic reduction of amides and related compounds using molecular hydrogen - Jose R. Cabrero-Antonino (Nature Portfolio, 2020)
Catalytic hydrogenation of amides is a pivotal chemical transformation for both research labs and chemical production in industry. Here, the authors comprehensively review this topic by including state-of-art homogeneous and heterogeneous catalysts that can hydrogenate amides and related compounds.